Variations of carbon monoxide concentrations in the Megacity of São Paulo from 2000 to 2015 in different time Scales - Rozante, José Roberto; Rozante, Vinícius; Alvim, Débora Souza; Manzi, Antônio Ocimar; Chiquetto, Júlio Barboza; D'Amelio, Monica Tais Siqueira; Moreira, Demerval Soares [UNESP] (MDPI, 2017)
Air pollution is an important public health issue. High levels of carbon monoxide in the atmosphere are hazardous to human health. Studies regarding the concentration of this and other gases in the atmosphere allow political actions to manage and reduce the emission of pollutants. In this context, this paper studied the annual, seasonal, weekly and daily variations of carbon monoxide (CO) concentration for the Metropolitan Region of São Paulo (MRSP).We studied three sites in the MRSP, two of them are located in areas under the influence of heavy vehicle traffic (Osasco and Congonhas) and the third one in a city park (Ibirapuera Park). The results showed high influence of gasoline vehicles on CO emission. In the annual scale, CO concentration decreased due to improvements in emission technology, despite the increasing number of vehicles. CO emission showed a seasonal, weekly and diurnal cycle associated to meteorological conditions and emission patterns. The highest values of mean concentration were observed in June/July for Osasco (2.20 ppm), Congonhas (2.04 ppm) and Ibirapuera (1.04 ppm), during the morning, due to weak dispersion of the polluting gases and higher emission from the rush hours.
Keywords: Carbon monoxide; Diurnal cycle; Pollution trends; Seasonal cycle; Urban pollution